Pengaruh Brand Image dan Promosi Online terhadap Keputusan Pembelian (Studi Kasus: Starbucks Coffee Surabaya MERR) - Frea Febri Salsabillah; Nuruni Ika Kusuma Wardani (Universitas Batanghari, 2023)
Indonesia is a country that also produces coffee and exports coffee beans on a world scale. The tropical climate and geographical conditions as well as favorable temperatures make Indonesia has excellent potential for coffee cultivation. Therefore, due to the abundance of coffee production in Indonesia, there are many kinds of processed coffee beans, one of which is coffee drinks. The habit of consuming coffee drinks for some people in Indonesia, especially in big cities like Surabaya, has become a lifestyle that continues to grow. This study was conducted to analyze the influence of brand image and online promotion on purchasing decisions at Starbucks coffee outlets. The population in this study is consumers who are interested and reside in Surabaya. This study uses a non-probability sampling method and also uses accidental sampling for sampling. With 99 respondents and analyzed using PLS. From the results obtained for this study, it is found that there is a positive influence between brand image, online promotion and purchasing decisions at Starbucks coffee outlets.